Dietary saturated and monounsaturated fats protect against acute acetaminophen hepatotoxicity by altering fatty acid composition of liver microsomal membrane in rats - Hwang, Jinah (BioMed Central, 2011)
BACKGROUND: Dietary polyunsaturated fats increase liver injury in response to ethanol feeding. We evaluated the effect of dietary corn oil (CO), olive oil (OO), and beef tallow (BT) on fatty acid composition of liver microsomal membrane and acute acetaminophen hepatotoxicity. METHODS: Male Sprague-Dawley rats were fed 15% (wt/wt) CO, OO or BT for 6 weeks. After treatment with acetaminophen (600 mg/kg), samples of plasma and liver were taken for analyses of the fatty acid composition and toxicity. RESULTS: Treatment with acetaminophen significantly elevated levels of plasma GOT and GPT as well as hepatic TBARS but reduced hepatic GSH levels in CO compared to OO and BT groups. Acetaminophen significantly induced protein expression of cytochrome P450 2E1 in the CO group. In comparison with the CO diet, lower levels of linoleic acid, higher levels of oleic acids and therefore much lower ratios of linoleic to oleic acid were detected in rats fed OO and BT diets. CONCLUSIONS: Dietary OO and BT produces similar liver microsomal fatty acid composition and may account for less severe liver injury after acetaminophen treatment compared to animals fed diets with CO rich in linoleic acid. These findings imply that types of dietary fat may be important in the nutritional management of drug-induced hepatotoxicity.